Penilaian Kapabilitas Pengembangan Perangkat Lunak Pada Perusahaan Pengembang Perangkat Lunak Menggunakan CMMI - DEV 1.3 (Studi Kasus PT. Cendana Teknika Utama) - Ahmad Muzakir Mahmud; Aditya Rachmadi; Mochamad Chandra Saputra (Jurnal Pengembangan Teknologi Informasi dan Ilmu Komputer, 2018)
PT.Cendana Teknika Utama is a company that focuses on product development in the field of mobile application, electronica control and web application. The products produced by the company are expected to support the demands of the current business development.But the fact that the products produced are still often found defects.This study aims to assess the level of product development process capability in one of the divisions in the company by using Capability Maturity Model Integration ( CMMI). The research method used is qualitative with data collection using interview and document search. Assessment stages were used using CMMI Appraisal Method for Process Improvement (SCAMPI) C class. Assessment was performed on six CMMI process areas selected based on the CMMI product roadmap. The six process areas consist of requirements development, requirements management, technical solution, process and product quality assurance, configuration management and verification. The result of the capability level assessment found that only the technical solution area process is at one level performed, while in other area process still at zero / incomplete level. From the results of the assessment conducted an analysis that contains solutions for companies to improve the level of capabilities